Association between transient tachypnea of the newborn and the results of auditory brainstem response - Fereshteh Bagheri; Zeinab Miresmaeili; Sima Tajik; Yadollah Zahedpasha (The Egyptian Journal of Otolaryngology)
Abstract Background Transient tachypnea of the newborn (TTN) is one of the reasons for admission of newborn to the neonatal intensive care unit (NICU). This study aimed to demonstrate the relationship between TTN and hearing loss and the results of auditory brainstem response (ABR) in Iranian infants. Methods We retrospectively examined 2591 infants referred to the audiology department of a children’s hospital in Northern Iran. Transient evoked otoacoustic emission (TEOAE) test was recorded in the first week of birth, and the ABR test was recorded in infants with a history of TTN after 3 months of age. Results A significant difference in the absolute latency of I, III, and V at 70 dBSPL clicks was seen in both ears of TTN infants. The results of this study showed a significant difference in IPL III–V, I–V in the right ear and IPL III–V in the left ear at 70 dBSPL clicks and also significant difference in absolute latency of III, V, and IPL III–V at 50 dBSPL clicks in both ears. Conclusions In general, our data confirmed that the performing ABR test in infants diagnosed with TTN is a necessity to evaluate the auditory system.